Edukasi Pentingnya Konsumsi Vitamin C bagi anak : Manfaat, Dosis dan Tanda Kekurangan di Sekolah Dasar Negeri 15 Kota Bengkulu: Edukasi Pentingnya Konsumsi Vitamin C bagi anak : Manfaat, Dosis dan Tanda Kekurangan di Sekolah Dasar Negeri 15 Kota Bengkulu - Aina Fatkhil Haque; Tri Yanuarto (Jurnal Pengabdian, 2023)
Health promotion activities between lecturers and students have been carried out at one of the elementary schools in Bengkulu City. This activity aims to provide information to students of SDN 15 Bengkulu City on the importance of vitamin C in terms of benefits, dosage, and signs of deficiency. This health promotion activity was carried out in collaboration with teachers and students of SDN 15 Bengkulu City. The form of activities that we carry out is delivering information on how to maintain endurance by utilising vitamin C. Using power points and forms of service, we provide samples of vitamin C, posters, snacks, and desserts. As well as questionnaires for students about how to maintain endurance by utilising vitamin C. All forms of efforts made can help students know and understand the kinds of ways to maintain endurance by utilising vitamin C. The results of the implementation activities that have been carried out on Tuesday, June 13, 2023, make students of SDN 15 Bengkulu City start to get used to eating fruits and vegetables and supplements that contain vitamin C. After the promotion, students can learn about the benefits of vitamin C found in many fruits, vegetables, and supplements.